2016
DOI: 10.1093/jac/dkw524
|View full text |Cite
|
Sign up to set email alerts
|

Electronic prescribing system design priorities for antimicrobial stewardship: a cross-sectional survey of 142 UK infection specialists

Abstract: SynopsisThe implementation of electronic prescribing and medication administration systems (EPMAs) is a priority for hospitals and a potential component of antimicrobial stewardship (AMS). ObjectivesThis study aimed to identify software features within EPMAs that could potentially facilitate AMS and to survey practising UK infection specialist healthcare professionals in order to assign priority to these software features. MethodsA questionnaire was developed using nominal group technique and transmitted via e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…We would argue that outputs from such systems, for example, prescription surveillance of missed doses,22 could also prompt action from nursing staff, though potential barriers to interprofessional collaboration have to be overcome. In addition, Wentzel et al note that to perform the complex antimicrobial-related tasks well, nurses need to consult various information sources on a myriad of occasions, and comment that hospital information infrastructure may be unsupportive of AS programme-related tasks, mainly because information is not structured to match nurse tasks, is hard to find, out of date and insufficiently supportive of AS programme awareness 23…”
Section: Discussionmentioning
confidence: 99%
“…We would argue that outputs from such systems, for example, prescription surveillance of missed doses,22 could also prompt action from nursing staff, though potential barriers to interprofessional collaboration have to be overcome. In addition, Wentzel et al note that to perform the complex antimicrobial-related tasks well, nurses need to consult various information sources on a myriad of occasions, and comment that hospital information infrastructure may be unsupportive of AS programme-related tasks, mainly because information is not structured to match nurse tasks, is hard to find, out of date and insufficiently supportive of AS programme awareness 23…”
Section: Discussionmentioning
confidence: 99%
“…24 Alert fatigue is a recognised risk of ePrescribing systems and must be balanced against added functionality and prescriber requirements to optimise possible outcomes. 15 Alert fatigue may have contributed to the difference seen between indication and stop and review date documentation. We also found that 12% of prescriptions had the mandatory indication 'over-ridden' using blank spaces or non-specific terms such as 'infection'.…”
Section: Discussionmentioning
confidence: 99%
“…There remains a pressing need for comprehensive and complete data to evaluate the intended and unintended impacts of AMS programmes in hospitals. However, although hospitals are clearly setting the course for e‐prescribing, full adoption and availability for secondary use might still take years. For now, linking HES to pharmacy data provides a potential mechanism to investigate some patient‐level drug usage across NHS hospitals.…”
Section: Discussionmentioning
confidence: 99%